ABC/VEN study of the list of medicines of the América Arias Gynecobstetric Teaching Hospital, Havana, 2021 - Gutiérrez-García, Daniela; García Fariñas, Anai; Elías-Díaz, Ingrid Elías-Díaz; Martínez-Álvarez, Igna María (Horizonte Sanitario, 2024)
Objective: To characterize the list of drugs used at the Hospital Docente Ginecobstétrico América Arias in 2021, according to their clinical and economic relevance, through the ABC/VEN matrix. Materials and Methods: A descriptive observational study was carried out that considered the number of medicines and the associated expenditure generated according to ATC therapeutic groups, country of origin, route of administration, ABC, VEN and ABC/VEN classification in the year 2021. Results: The Medicines List included 358 products. There were 25 medicines in category A, representing 3 essential medicines, 3 special medicines, 18 vital medicines and 1 non-essential medicine but representing high consumption in category A; with a total group expenditure of 3,724,633.42 CUP, 75 medicines in category B, with an expenditure of 1,037,713.04 CUP and 258 medicines in category C, with an expenditure of 229,885.20 CUP. Conclusions: The application of ABC-VEN analysis allowed effective clinical-economic classification of drugs. The high presence of antimicrobials underscored the need to strengthen microbiological surveillance and the performance of antibiograms. The inclusion of non-essential drugs with high cost (vaginal Ketoconazole) should be reviewed. The combination of ABC and VEN methods allowed a more exhaustive control of critical drugs, optimizing the use of the hospital budget. Keywords: List of essential drugs, ABC Analysis, VEN Analysis, ABC/VEN Matrix.